1 - La domestication des étudiants du campus de Ouagadougou : la crise de juin 2008 - Lila Chouli (Journal of Higher Education in Africa, 2009)
After several months of latency, the conflict between the students of two departments of the university of Ouagadougou and the academic authorities turned into an open crisis in June 2008 – the most serious one since the reorganization of the university and the invalidation of the academic year in 2000 – symbolized by the return of soldiers to the campus, the confron- tations between police and students and the suspension of student social support services.By evaluating this crisis in the context of a longer period – that of the post-revolutionary regime – this article demonstrates how the authorities seized the opportunity to make case for a takeover of the university of Ouagadougou. This University traditionally had been one of the centres of political protest, a reality in the context of the return of sectorial mobilizations. As was often the case, this process was facilitated by the resort to the legal system as an instrument of repression of the social movement, the use of interest conflicts between the students, the very difficult living conditions of the students who depended on social support, and the risk of a “white year”.